Creative Design Workshop and Training with the title "Transforming Ideas into Works: Honing Creativity in Design" - MUHAMMAD ABDUL JABBAR; RIFQI SYAMSUL FUADI (Community Service Journal : Jurnal Pengabdian Masyarakat Mardira, 2025)
This community service through workshops and creative design training activities is carried out as a form of contribution to increasing the capacity of the community in visual communication or expressing into the visual aspects of a concept or idea. The main goal of this activity is to transfer basic knowledge about the principles of graphic design and develop the ability of participants to pour ideas into a form of visual work that is communicative and has aesthetic value. The training is conducted with a participatory approach that combines theory and practice in a balanced manner, using digital media such as CorelDRAW Graphics Suite 2022 to facilitate the learning process. Participants consisted of 12th grade high school/vocational/MA students from several schools from Majalengka Regency and Cirebon Regency who had needs in developing visual content for 3 days. The results of the activity showed an increase in the knowledge and skills of participants in creating designs independently, as well as a growing awareness of the importance of creativity in supporting personal activities and in daily life. This activity also proves that graphic design training can be a means of empowering the community in facing challenges in the digital era. It is hoped that similar activities can be carried out on a sustainable basis so that the impact is wider and more evenly distributed from various circles, not only for students.